2021
DOI: 10.3892/etm.2021.10752
|View full text |Cite
|
Sign up to set email alerts
|

Gigantol inhibits cell proliferation and induces apoptosis by regulating DEK in non‑small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is a common type of cancer, with a mortality of >80% worldwide. Gigantol is a bibenzyl compound that displays anticancer activity. The aim of the present study was to determine the biological activity of gigantol in NSCLC and to elucidate the underlying molecular mechanism of its action. The expression of DEK proto-oncogene (DEK) was measured in NSCLC tissues and cell lines by reverse transcription-quantitative PCR (RT-qPCR). The results suggested that DEK levels were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Additionally, DEK is overexpressed in high-grade serous ovarian cancers (HGSOCs), and reducing DEK levels significantly reduces cell viability and tumor growth, resulting in apoptotic cell death [ 38 ]. Cai et al showed that Gigantol inhibits cell proliferation and induces apoptosis by regulating DEK in non-small cell lung cancer [ 39 ]. In the report on GC, Lee et al reported that DEK is a potential biomarker associated with malignant phenotype in GC Tissues and Plasma [ 40 ], and Fan et al demonstrated that circ_0000039 upregulates DEK expression by adsorbing miR-1292-5p, promoting the proliferation and progression of GC cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DEK is overexpressed in high-grade serous ovarian cancers (HGSOCs), and reducing DEK levels significantly reduces cell viability and tumor growth, resulting in apoptotic cell death [ 38 ]. Cai et al showed that Gigantol inhibits cell proliferation and induces apoptosis by regulating DEK in non-small cell lung cancer [ 39 ]. In the report on GC, Lee et al reported that DEK is a potential biomarker associated with malignant phenotype in GC Tissues and Plasma [ 40 ], and Fan et al demonstrated that circ_0000039 upregulates DEK expression by adsorbing miR-1292-5p, promoting the proliferation and progression of GC cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer cell line A549, gigantol has been shown to suppress cell proliferation and enhance apoptosis in tumor cells at a concentration of 25, 50, and 100 µM. Investigators report these effects to be mediated by inhibition of Bcl-2 expression and upregulation of Bax expression and Wnt/β-catenin signaling [224]. In another study, gigantol has been shown to inhibit cell proliferation in H460 lung cancer cells at a concentration of 50 µM.…”
Section: Gallic Acidmentioning
confidence: 98%
“…Additionally, treatment with 20 μM Andro caused an essential decrease in the mitochondrial membrane potential (MMP), an increase in Bak mitochondrial translocation, and an increase in the activation of proteins in the mitochondrion-mediated intrinsic apoptosis pathway. 38 TA B L E 3 (Continued)…”
Section: Targeting Bcl-2 Family Proteinsmentioning
confidence: 99%
“…Among these derivates, Compound 17 (38) exerted excellent anticancer activity against H460 and H322 cells (IC 50 = 2.6 ± 0.9 μM and 3.3 ± 0.9 μM, respectively). It induced autophagy by TA B L E 4 (Continued)…”
Section: Targeting Beclin-1mentioning
confidence: 99%
See 1 more Smart Citation